2016
DOI: 10.1097/md.0000000000004955
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of minimally invasive plate osteosynthesis and conventional plate osteosynthesis for humeral shaft fracture

Abstract: Background:The objective of this meta-analysis was to compare the efficacy and safety of minimally invasive plate osteosynthesis (MIPO) and conventional plate osteosynthesis (CPO) for humeral shaft fracture.Methods:Potential academic articles were identified from the Cochrane Library, Medline (1966–2016.3), PubMed (1966–2016.3), Embase (1980–2016.3), and ScienceDirect (1966–2016.3). Gray studies were identified from the references of the included literature. Randomized controlled trials (RCTs) and non-RCT invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 27 publications
(39 reference statements)
1
16
0
2
Order By: Relevance
“…Según el metanálisis de Yu y cols., una de sus ventajas es la reducción del riesgo de daño del nervio radial, tendencia que también se observó en nuestro estudio. 15 Uno de los principales temas por estudiar es la reducción del riesgo de daño del nervio radial. En algunos casos tratados con la técnica abierta convencional, el simple hecho de su identificación y la protección nerviosa pueden provocar una neuropraxia posquirúrgica.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Según el metanálisis de Yu y cols., una de sus ventajas es la reducción del riesgo de daño del nervio radial, tendencia que también se observó en nuestro estudio. 15 Uno de los principales temas por estudiar es la reducción del riesgo de daño del nervio radial. En algunos casos tratados con la técnica abierta convencional, el simple hecho de su identificación y la protección nerviosa pueden provocar una neuropraxia posquirúrgica.…”
Section: Discussionunclassified
“…23,24 La técnica MIPO tampoco aumenta el riesgo de complicaciones en general, según el estudio de Yu y cols., lo que es ventajoso, porque la comparación se realizó con la técnica de fijación con placa convencional, considerada el patrón de referencia. 15 En relación con la metodología del estudio, nos llamó la atención la disparidad de casos entre un centro hospitalario (Paraguay). Esto determina que, en la estadística general, diluya los resultados de los otros dos centros, y le resta potencia estadística a nuestro trabajo, así se menciona que, en variables, como las complicaciones, estas hayan sido en su mayoría del Paraguay, lo que podría no ser completamente representativo de la técnica.…”
Section: Discussionunclassified
“…Although there are clear advantages and disadvantages of minimally invasive approaches to fracture stabilization compared with open approaches, the human and veterinary literature is not clear and is often conflicting with regard to developing a cost–benefit analysis for these cases. For example, one metanalysis by Yu et al presented some evidence that operating times were not statistically different when MIPO was compared with more traditional techniques. However, in another metanalysis, Li et al showed that minimally invasive approaches were associated with longer operating times.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the presence of multiple reports of studies describing and advocating the use of MIO and MIPO techniques in both the veterinary and human literature, conflicting evidence still remains about the direct benefits of these approaches compared with more traditional rigid internal fixation techniques . The veterinary literature to date has focused on objective benefits but has not identified whether these techniques are widely performed by the veterinary orthopedic community.…”
Section: Introductionmentioning
confidence: 99%
“…15 A meta-analysis by Yu et al. 16 showed that the incidence of nonunion and delayed union was lower in the MIPO group than CPO group. However, the difference was negligible which was also observed in the study by Esmailiejah et al.…”
Section: Discussionmentioning
confidence: 99%